Case Report: “Aggressive” perioperative antiseizure medication prophylaxis in patients with glioma-related epilepsy at high risk of early postoperative seizures following awake craniotomy - Freund, Brin E.; Jaeckle, Kurt; Quinones-Hinojosa, Alfredo; Feyissa, Anteneh M. (Frontiers in Surgery, 2024)
Early postoperative seizures (EPS) are a common complication of brain tumor surgery. EPS can lead to hemorrhage, cerebral hypoxia, increased intracranial pressure, longer hospitalization, reduced quality of life, decreased overall survival, and increased morbidity. However, there are no formal guidelines on perioperative antiseizure medication (ASM) management in patients with tumor-related epilepsy who are deemed high risk for EPS. In this study, we describe the case of a 38-year-old man with isocitrate dehydrogenase-mutant mixed glioma and two episodes of EPS manifesting with status epilepticus during prior tumor surgeries and who presented with tumor progression. The Tumor Board recommended awake craniotomy with direct electrical stimulation (DES). The patient was administered aggressive preoperative “prophylactic” ASMs by increasing the maintenance doses of lacosamide and levetiracetam by 25% 48 h before surgery. An intravenous load of fosphenytoin (20 mg/kg) was administered in the operating room before DES, followed by a maintenance dosing of 300 mg/day for 14 days. EPS did not occur, and he was discharged home on postoperative day 4. Our case illustrates that aggressive perioperative prophylactic ASM therapy beyond the maintenance ASM regimen can be considered in patients with tumor-related epilepsy at risk of EPS.